A comparison of accelerometer cut-points for measuring physical activity and sedentary time in adolescents with Down syndrome. (January 2022) - Forseth, Bethany; Carlson, Jordan A.; Willis, Erik A.; Helsel, Brian C.; Ptomey, Lauren T.
Highlights: There are no accelerometer cut-points specific to youth with Down syndrome (DS). Applying non-DS cut-points to those with DS may lead to variation in results. Caution is advised when comparing activity results that use different cut-points. Validated DS cut-points would account for physiologic and biomechanical differences. Abstract: Background: No cut-points have been developed for youth with Down syndrome; there is concern that altered gait patterns, decreased energy expenditure and exercise capacity of individuals with Down syndrome may produce inaccurate physical activity data if accelerometer data are analyzed using cut-points from populations with typical development and other IDD diagnoses. Aim: To compare physical activity and sedentary time across existing accelerometer cut-point methods in adolescents with Down syndrome. Methods: In this cross-sectional analysis, participants diagnosed with Down syndrome (n = 37; 15.5 ± 1.9 years; 57 % female) wore an accelerometer on their non-dominant hip for seven-days. Data were analyzed and compared across four physical activity intensity cut-points: Evenson, Freedson 4-MET, McGarty, and Romanizi. Outcomes & results: Differences in time spent in each intensity across cut-point methods were evident for sedentary (448−615 min/day), light (72−303 min/day) and moderate-to-vigorous (12−77 min/day) activities. Between 0.0–67.6 % of the sample met the physical activity guidelines, depending on the cut-point method selected. Conclusions & implications: This study presents the wide variation of accumulated physical activity minutes when different cut-points are applied to individuals with Down syndrome. There is a critical need to establish Down syndrome-specific measures of physical activity assessment rather than applying methods developed for their peers with typical development. What this paper adds: This paper highlights concerns over the application of objective measurements of physical activity in youth with Down syndrome from measurement methods derived from populations with typical development. This is the first manuscript to examine this issue in a sample comprised solely of youth with Down syndrome. Results demonstrate the large variation in time spent in each activity intensity that arise due to the application of different cut-point methods.